Effect of pore size on the current produced by 3-dimensional porous microbial anodes: A critical review. (October 2019) - Chong, Poehere; Erable, Benjamin; Bergel, Alain
Graphical abstract: Highlights: Internal colonization and current density are analysed with respect to the pore sizes. Small pore sizes, below 10 µm, produced the lowest current density. Pore sizes ranging from 10 to 100 µm showed pore clogging by the biofilm. Pores from 100 to 500 µm allowed internal colonization but limited mass transport. Pores sizes at millimetre(s) level produced the highest current density. Abstract: Microbial anodes are the cornerstone of most electro-microbial processes. Designing 3-dimensional porous electrodes to increase the surface area of the electroactive biofilm they support is a key challenge in order to boost their performance. In this context, the critical review presented here aims to assess whether an optimal range of pore size may exist for the design of microbial anodes. Pore sizes of a few micrometres can enable microbial cells to penetrate but in conditions that do not favour efficient development of electroactive biofilms. Pores of a few tens of micrometres are subject to clogging. Sizes of a few hundreds of micrometres allow penetration of the biofilm inside the structure, but its development is limited by internal acidification. Consequently, pore sizes of a millimetre or so appear to be the most suitable. In addition, a simple theoretical approach is described to establish basis for porous microbial anode design.